Միջարկության լեզվաբանական ըմբռնման զարգացումը անգլերենում - Գոհար Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
Дисциплинарная неоднородность междометий в истории лингвистики привела к проблеме классификации этих выражений, рассматривая их как словесное выражение духовной сущности человека-эмоций, воли и мысли. The disciplinary inhomogeneity of interjections in the history of linguistics has led to the problem of classification of these expressions, treating them as verbal expression of the spiritual essence of the person-emotions, will and thought.
Keywords: Language and Literature; English